Collaborative disaster management system - An exploratory for landslide in Malaysia - Salem Almohaifer, Mohammad; Mohamed A. Islam, Dramane; Azad, Abul Kalam; Ahmad Dahlan, Abdul Rahman (University Sultan Zainal Abidin, 2011)
A disaster management system has active, unpredictable, and complex characteristics due to dynamic conditions with a high level of uncertainty. Non-Government Organizations (NGO)and Government organizations from different jurisdictions and sectors with different responsibilities at regular times create an emergent and complex system in response to disasters. Although being mostly demanded, the collaboration initiatives between government agencies that specifically designed to address risk management before a disaster happens is lacking in effectiveness. In the Malaysian perspective, there are organizations, such as the Public Works Department (PWD), Department of Mineral and Geosciences (DMG) and Centre of Remote Sensing (MACRES)that are involved in mitigation and preparedness of landslides disasters, but results are not encouraging due to the need of effective collaboration among these organizations. It is natural for humans to collaborate while dealing with complex problems. In this regard, we consider this process of effective collaboration in the context of information systems. Investment in the information technologies and systems, and its utilization can play a critical role in creating a complex socio-technical disaster system to coordinate organizations and jurisdictions in dynamic settings. We propose a simple model for collaboration that helps us to realize a successful risk management in disasters. A model of Collaborative Disaster Management System is then rendered based on an extended model of management of information systems